Pengaruh Gaya Kepemimpinan Kepala Madrasah terhadap Efektivitas Madrasah Aliyah Swasta Provinsi Kepulauan Riau - Achmad Fauzi (TADRIBUNA: Journal of Islamic Education Management, 2026)
This study aims to determine the effect of the leadership style of madrasah principals on the effectiveness of senior high madrasahs. This quantitative study employs a survey method. The study population consists of all teachers at private senior high schools in the Riau Islands Province. The sample size is 61, selected using a total sampling technique. Data analysis employs simple linear regression, supplemented by validity tests, reliability tests, classical assumption tests, and a coefficient of determination test. The results indicate that the principal’s leadership style significantly influences the effectiveness of the madrasah by 40.412, with a significance level of 0.000. The calculated t-value exceeds the critical t-value (40.412 > 2.004) at a significance level of less than 0.05 (0.05 > 0.000). The R-squared value is 0.965, indicating that the principal’s leadership style accounts for 96.5 percent of the variation in madrasah effectiveness, while 3.5 percent is influenced by other independent variables not examined in this study. These findings indicate that the leadership style of the madrasah principal is a dominant factor in improving Madrasah Effectiveness at private Madrasah Aliyah in the Riau Islands. Developing adaptive, democratic, transformational, and innovative leadership styles through training, supervision, and capacity-building for madrasah principals by the foundation and the Ministry of Religious Affairs to sustainably improve the quality and competitiveness of private senior high schools in the Riau Islands Province.